Antibacterial activities of daldina concentrica (2011)
Activities of the distilled water, ethanolic and chloroform extracts of Daldina concentrica an ascomycetous fungus was investigated on Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, Bacillus cereus and Staphylococcus aureus) using agar well diffusion method. Ethanolic extract of Daldina concentrica showed significantly antibacterial activity against all the test microorganisms except Bacilllus cereus (P ≤0.05). Staphylococcus aureus was the most sensitive organism to the extracts of this fungus with 17.0mm zone of inhibition with ethanol extract. It was also shown that chloroform extract of Daldinia concentrica possessed higher anti-bacterial activity against the five tested microorganisms. The effect of fresh tissues of the fungus on test bacteria indicated that Proteus mirabilis was the only sensitive organism with 5.0mm zone of inhibition while other bacteria were resistant. The implications of these findings were discussed.